1984
DOI: 10.1177/1077727x8401300109
|View full text |Cite
|
Sign up to set email alerts
|

Cookery Methods for Vegetables: Influence on Sensory Quality, Nutrient Retention, and Energy Consumption

Abstract: Ten different fresh vegetables were prepared by four cooking methods: boiling, steaming, pressure cooking and microwaving. Vegetables prepared by the dif ferent techniques were evaluated by descriptive sensory analysis using a small, trained group of judges. Ascorbic acid retention and electrical energy consump tion were also measured for each cooking method. No single cooking method consistently produced the product that was judged to be most like the sensory ideal. Vegetables prepared by pressure cooking, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…No data had been previously reported for microwave steaming methods. However, the results of this study tend to support the findings of other researchers who have shown that no one ideal method exists for the preparation of vegetables with optimum sensory qualities (Warthesen et al 1984;Johnson and Driskell 1987). This may be due to differences between cooking fresh and frozen vegetables and strong and mild flavored vegetables.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…No data had been previously reported for microwave steaming methods. However, the results of this study tend to support the findings of other researchers who have shown that no one ideal method exists for the preparation of vegetables with optimum sensory qualities (Warthesen et al 1984;Johnson and Driskell 1987). This may be due to differences between cooking fresh and frozen vegetables and strong and mild flavored vegetables.…”
Section: Resultssupporting
confidence: 76%
“…Much research was done in the 1950's and 1960's in this area. However, as Warthesen et al (1984) point out, more research is needed. New cultivars of plants now exist, changes in consumer preferences toward the consumption of more crisp vegetables are evident, and the widespread availability of microwave cooking will affect nutrient content of vegetables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cooking vegetables in the microwave, the energy conserved is 52%, 68%, and 83% of the energy used to steam, boil, and bake vegetables. Also, the reduction in cooking time was 50%, 61%, and 71% less than for steaming, boiling, and baking, respectively (Warthesen et al 1984). Electric stoves require about 822 kWh/year and gas and liquid petroleum gas stoves require 1,600 kWh/year, whereas microwaves need only 132 kWh/year (Wenzel et al 1997).…”
Section: Microwavementioning
confidence: 98%
“…Ilow et al (1995) compared the effect of cooking vegetables (cauliflower, white cabbage, Brussel sprouts, French bean, and potatoes) by microwave, pressure-cooking or conventional cooking (i.e., boiling in cold water) with uncooked controls; average losses of AA were 13.9, 32.8, 37.8 and 53.3 %, respectively. Warthesen et al (1984) reported that 67.8 and 78.6 % of AA was retained in spinach and green beans, respectively that had been cooked in a microwave but after boiling, these levels dropped to 33.9 and 63.7 %, respectively. Thus, boiling in water leads to a decrease in AA content.…”
Section: Ascorbic Acidmentioning
confidence: 99%